Hubungan Antara Kemampuan Berempati Dan Self Esteem Dengan Perilaku Prososial Pada Remaja - Ayu Dewanti, Windha, Rini Lestari, S.Psi, M.Si (2016)
Human is social creatures, they can not let himself not to interact with social around. But in this era where everything is mobilize and modern, gives huge impact to people especially teenager, so it brings friction to interact pattern over individual and changed values in social life. These days we common found teenager do something antisocial rather than prosocial. Teenager needs have a sense of empathy and self-esteem to raise prosocial behavior among them.The purpose of this research are 1. to know the connection between abbility to empathy and self-esteem toward prosocial behavior in teennager. 2. to know level of empathy, self-esteem and prosocial behavior . 3. to know the role of the abbility to empathy and self-esteem toward prosocial behavior.This research used purposive sampling technique with 100 students from SMA Batik 1 Surakarta. The data were collected through ability to empathy scale, self esteem scale, and prosocial behavior scale. The data were analyzed by regression analysis. Based on regression analysis, correlation coefficient values (rxy) has obtained 0.797; p= 0,000 (p < 0,01) which is shown great significant connection between the abbility to empathy and self-esteem toward prosocial behavior among teenager. Effective contribution the abbility to empathy and self-esteem are 63,5% and the rest about 36,5% obtained from another variables. The abbility to empathy is very high shown by empirical mean 86,50, and then the self-esteem is very high also shown by empirical mean 55,24, while prosocial behavior shown by empirical mean 101,04. Keywords:Prosocial behavior, Self esteem, Ability to empathy.